IMPLEMENTASI NILAI DAN SIKAP PANCASILA DALAM PENGEMBANGAN SOAL HOTS DAN LOTS UNTUK SISWA KELAS V SD FASE B - Silfiani, Humaira; Mauluah, Luluk; Sunaryo, Ikhwan; Andini, Arfah (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to describe the implementation of Pancasila values and attitudes in the development of Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) assessment items for elementary school students in Phase B. The research employed a descriptive qualitative approach using a library research method, drawing on various scientific sources such as journal articles, academic textbooks, and curriculum documents. The results indicated that LOTS focuses on basic thinking skills, including remembering, understanding, and applying (C1–C3), while HOTS involves higher-level thinking skills such as analyzing, evaluating, and creating (C4–C6). The integration of Pancasila values into the construction of HOTS and LOTS items contributes significantly to fostering students’ national, moral, and humanitarian character. In conclusion, the development of HOTS- and LOTS-based assessment instruments grounded in Pancasila values can assist teachers in creating meaningful, active, and character-oriented learning processes at the elementary school level.